La Theorie der Unbildung di Konrad Paul Liessmann - Marcone, Francesca (Studi sulla Formazione/Open Journal of Education, 2023)
The article focuses on a German-language essay written by Konrad Paul Liessmann in 2006, entitled Theorie der Unbildung. Die Irrtümer der Wissensgesellschaft (Theory of Unbildung. The mistakes of the knowledge society). In this book, the Austrian philosopher dwells on the relationship between the concepts of “Wissen” (knowledge) and "Bildung” (human formation) in contemporary society. With his pedagogical critique, Liessmann formulates here a theory of Unbildung, with a direct reference to the absence of human self-formation – so evident nowadays.